Qenja: child fostering and relocation practices in the Amhara region, Ethiopia. Issue 1 (2nd January 2016) - Kassa, Sophia Chanyalew; Abebe, Tatek
Abstract : In this article we discuss temporary relocation and informal labour of children in rural Ethiopia. We respond to the call 'to understand the wider logic underlying child relocation and non-parental residence among populations experiencing poverty' (Boyden, J. 2013. "We're Not Going to Suffer Like this in the Mud: Educational Aspirations, Social Mobility and Independent Child Migration among Populations Living in Poverty." Compare: A Journal of Comparative and International Education 43 (5): 580–600. 582). Drawing on the perspectives of children and families involved in the practice of qenja (meaning 'teaming' or 'forming a coalition') we examine how – in contexts of uneven distribution of rural labour – children's involvement in transient agricultural labour outside the home is a fundamental feature of social reproduction. We argue that qenja is a social coping strategy that co-exists alongside gendered and generational relations of household production and reproduction. An understanding of the practice as merely transactional and exploitative ignores long-standing community strategies of labour acquisition and redistribution. We stress that child protection campaigns by non-governmental organizations and national legislations that intend to criminalize the practice are not in the interest of children, families, and communities.